Changing Relations: Power, Ethics and Responsibility In Graduate Supervision - Valerie-Lee Chapman; Thomas J. Sork (Adult Education Research Conference, 1998)
This paper continues the dialogue between a feminist graduate student and non-feminist male advisor in an adult education graduate program: they each define the power relations inherent in the relationship, and raise questions about their ethical and moral responsibilities.